Is there an heir apparent to the Crown? A more informed understanding of connectivity and networked environmental governance in the Crown of the Continent - Bixler, Richard Patrick, author; Taylor, Peter Leigh, advisor; Carolan, Michael S., committee member; Cross, Jennifer E., committee member; Cheng, Antony S., committee member (Colorado State University. Libraries, 2014)
Multi-actor and multi-level processes characterize contemporary environmental governance where a multiplicity of actors and modes of governance are operating in diverse and overlapping spheres of authority. No fixed spatial or temporal level is appropriate for governing ecosystems and their services sustainably, effectively, and equitably. Rather, ecological processes interact across a range of spatial scales, which has led to an increased interest in the way networks operate and govern environmental processes across landscapes. These governance schemes involve communication and coordinated action by federal, state, and local agencies working with private landowners, nonprofit organizations, and industry. They involve multiple, interconnected issues within contexts that are complex, dynamic, and involve uncertainties. Working across multiple levels reveals governance and coordination challenges that often outstrip capacities, structures, and decision-making processes of the individuals or organizations involved. The processes of initiating multi-actor governance is not politically neutral, nor does it exist in a vacuum. It rather reflects competing interpretations of the appropriate distribution of power in a network and how information and knowledge are created and acted upon for environmental governance. Through this dissertation, I maintain that making progress towards these challenges requires a concerted effort and focus on the role of community-based conservation within the broader and emerging cross-scale networks of environmental governance. These cross-scale networks of landscape governance can either strengthen the role of community-based natural resource management or undermine them. To this end, my dissertation entitled: "Is there an Heir Apparent to the Crown? A More Informed Understanding of Connectivity and Networked Environmental Governance in the Crown of the Continent" uses social network analysis and qualitative interviews to explain the mechanisms that nurture cross-scale linkages that enhance collaborative community capacity in environmental governance. Building on a fundamental premise of landscape conservation, ecological connectivity, I develop three conceptual ideas in this dissertation: that social connectivity is a necessary prerequisite for network governance and landscape-scale conservation. Social connectivity includes concepts of social networks and is concerned with how information flows between individuals and organizations. Discourse connectivity is that crucial next step that links the social and the ecological together through a process of narrative and problem framing. Finally, I develop the idea of assemblage connectivity. The interest here is how the previous three concepts (ecological, social, and discourse) catalyze the conditions for cross-scale conservation that strengthens the role of community-based natural resource management. This framework is then applied across three empirical issue 'case-studies', invasive species management, grizzly bear conservation, and climate adaptation.
Keywords: community-based conservation; crown of the continent; environmental governance; landscape conservation; multi-level governance; social networks